Magnetic field and internal heat generation effects on the free convection in a rectangular cavity filled with a porous medium saturated with Cu–water nanofluid. (January 2017) - Rashad, A.M.; Rashidi, M.M.; Lorenzini, Giulio; Ahmed, Sameh E.; Aly, Abdelraheem M.
Highlights: The effect of magnetic field and internal heat generation on the free convection is investigated. The cavity is filled with a porous medium saturated with Cupper Cu–water nanofluid. A broad range of Hartmann numbers is employed. A broad range of solid volume fraction is employed. Isotherms, streamlines, average Nusselt number, velocity and temperature profiles are displayed. Abstract: The present study investigates the effect of magnetic field and internal heat generation on the free convection flow in a rectangular cavity. Here, the cavity is filled with a porous medium saturated with Cupper Cu–water nanofluid. The governing equations are transformed into dimensionless form in stream function and solved numerically using finite difference method. The computations were carried out for a wide range of the Hartmann number, solid volume fraction and magnetic field parameter. Results have been presented in terms of the isotherms, streamlines, average Nusselt number, velocity and temperature profiles. The obtained results are compared with the previous published work and it showed a good agreement. It is found that the average Nusselt number decreases as the Hartmann number or the solid volume fraction increases, while the opposite behavior occurs with the increase in magnetic field inclination angle. Moreover, the increase in the Hartmann number leads to decrease the maximum value of stream function, while it enhances the maximum temperature.